Marketing and information technology : - O'Connor, John (Pitman, 1997)
This is a comprehensive overview of the relationship between marketing and information technology using practical examples and case studies. This guide shows for both marketing and IT professionals how to unleash the potential of IT. Each chapter includes learning objectives and assignment questions. Topics include: the changing role of IT in marketing and the potential of new technologies; hot concepts, such as relationship marketing and micro segmentation; customer databases and information warehouses; the role of IT in customer services and sales; and selecting and implementing marketing systems. The final chapter on future developments covers expected future trends in the area of marketing information systems